2021
DOI: 10.3390/toxins13020131
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxin Gene Distribution and Genotypes of Bacillus cereus sensu lato Isolated from Cassava Starch

Abstract: Bacillus cereus is a human pathogenic bacterium found in foods with the potential to cause emesis and diarrhea. This study estimated the presence, toxigenic and genomic diversity of B. cereus s.l. obtained from cassava starch samples collected in bakeries and powdered food companies in Medellín (Colombia). Bacillus cereuss.l. was found in 43 of 75 (57%) cassava starch samples and 98 isolates were obtained. The nheABC, hblCDAB, cytK2, entFM and cesB toxin genes were detected by multiplex PCR and the most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(80 reference statements)
3
2
0
Order By: Relevance
“…The rest include strains from different markets. On the one hand, this study evidences the wide genetic diversity of B. cereus strains previously described in other food matrices with this same technique ( Sánchez-Chica et al, 2021a ; Sánchez-Chica et al, 2021b ; Samapundo et al, 2011 ; Samapundo et al, 2014 ). On the other hand, the concentration of coriander producers in the markets coming from different locations near the region, with possible differences in pre-harvest, harvest, and post-harvest stages, could explain this genetic diversity.…”
Section: Discussionsupporting
confidence: 80%
“…The rest include strains from different markets. On the one hand, this study evidences the wide genetic diversity of B. cereus strains previously described in other food matrices with this same technique ( Sánchez-Chica et al, 2021a ; Sánchez-Chica et al, 2021b ; Samapundo et al, 2011 ; Samapundo et al, 2014 ). On the other hand, the concentration of coriander producers in the markets coming from different locations near the region, with possible differences in pre-harvest, harvest, and post-harvest stages, could explain this genetic diversity.…”
Section: Discussionsupporting
confidence: 80%
“…The rest include strains from different markets. On the one hand, this study evidences the wide genetic diversity of B. cereus strains previously described in other food matrices with this same technique (Sánchez-Chica et al, 2021a;Sánchez-Chica et al, 2021b;Samapundo et al, 2011;Samapundoet al, 2014). On the other hand, the concentration of coriander producers in the markets coming from different locations near the region, with possible differences in pre-harvest, harvest, and postharvest stages, could explain this genetic diversity.…”
Section: Discussionsupporting
confidence: 80%
“…According toWehrle et al (2010), the incidence of ces gene in B. cereus species strains is low, generally less than 5%. In harmony with this,Chon et al (2015),Fogele et al (2018),Park et al (2018) andSánchez-Chica et al (2021), did not find any ces genes in all the spice, ready to eat vegetables, vegetable and cassava starch samples they analyzed, respectively. Moreover,Ceuppens et al (2011) andFrentzel et al (2016) reported only 1.5% and 1.7% of their samples to contain the ces gene.…”
supporting
confidence: 64%